Low-dose aspirin and rivaroxaban combination therapy to overcome aspirin non-sensitivity in patients with vascular disease - Hamzah Khan; Mariya Popkov; Shubha Jain; Niousha Djahanpour; Muzammil H. Syed; Margaret L. Rand; Margaret L. Rand; John Eikelboom; John Eikelboom; C. David Mazer; C. David Mazer; Mohammed Al-Omran; et al. (Frontiers in Cardiovascular Medicine, 2022)
Approximately 20% of vascular patients treated with acetyl salicylic acid (i.e., aspirin) demonstrate less than expected platelet inhibition – putting them at a four-fold increased risk of adverse cardiovascular events. Low-dose rivaroxaban (2.5 mg twice daily) in combination with low-dose aspirin has been shown to reduce adverse cardiovascular and limb events when compared to aspirin alone. In this study, light transmission aggregometry was used to measure arachidonic acid-induced platelet aggregation to evaluate the potential of combining low-dose rivaroxaban and aspirin in attenuating or overcoming aspirin non-sensitivity. In the discovery phase, 83 patients with peripheral arterial disease (PAD) taking 81 mg aspirin daily were recruited from the outpatient vascular surgery clinic at St Michael's Hospital between January to September 2021. 19 (23%) were determined to be non-sensitive to aspirin. After ex-vivo addition of 2.5 mg dosage equivalent of rivaroxaban, aspirin non-sensitivity was overcome in 11 (58%) of these 19 patients. In the validation phase, 58 patients with cardiovascular risk factors who were not previously prescribed aspirin were recruited. In this group, ex-vivo addition of 2.5 mg dosage equivalent of rivaroxaban significantly reduced arachidonic acid-induced platelet aggregation in the presence of aspirin. These results demonstrate the potential for low-dose rivaroxaban to overcome aspirin non-sensitivity in patients with PAD. Further studies are needed to evaluate and confirm these findings.